Internalisasi Nilai-Nilai Tauhid dalam Menghadapi Tantangan Kecerdasan Buatan (Artificial Intelligence): Perspektif Pendidikan Islam Kontemporer - Bahrum Saleh (Medan Resource Center, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed educational practices, knowledge production, and human interaction, while simultaneously raising ethical, spiritual, and epistemological challenges for Muslim learners in the digital era. This study examines how the internalization of tawhid values can serve as a foundational framework for addressing the opportunities and risks posed by AI within the context of contemporary Islamic education. The central question investigates the role of tawhid-based education in shaping learners’ ethical awareness, spiritual resilience, and critical engagement with intelligent technologies. Employing a qualitative library research approach, this study analyzes contemporary literature on Islamic educational philosophy, AI ethics, and the concept of tawhid as a holistic worldview. The findings reveal that the internalization of tawhid values strengthens moral responsibility, cultivates critical digital literacy, reinforces human accountability before God, and prevents technological determinism that may undermine religious and ethical consciousness. Integrating tawhid into educational curricula encourages learners to utilize AI as a tool for human flourishing rather than as an autonomous authority governing human decisions. The study argues that tawhid-oriented Islamic education offers a comprehensive paradigm for balancing technological innovation with spiritual integrity, thereby preparing Muslims to navigate the complexities of the AI era responsibly and ethically.